Biological Drinking Water Treatment? Naturally. Issue 12 (1st December 2015) - Brown, Jess; Summers, R. Scott; LeChevallier, Mark; Collins, Heather; Roberson, J. Alan; Hubbs, Steve; Dickenson, Eric
Abstract : At a 2013 AWWA symposium on biological treatment of drinking water, presentations covered a full spectrum of topics; speakers outlined different processes, dispelled misconceptions, introduced new research, and summarized the regulatory aspect of biotreatment.